2012
DOI: 10.4028/www.scientific.net/amr.545.235
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Hydroxyapatite Extracted from Fish Scales

Abstract: In this study, hydroxyapatite (HAp) was extracted from freshwater fish scales and saltwater fish scales using thermal decomposition method at various temperatures. The percentages of HAp in each species of raw fish scales were analysed using thermogravimetry analysis (TGA) whereas Fourier transform infrared (FTIR) was used to confirm the present of HA. The crystallinity of the HAp was studied using x-ray diffractometer (XRD). TGA and FTIR are found to be useful techniques to predict the composition of the HAp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…However, in consideration of the high cost associated with chemicals used in the synthetic process, other natural sources were explored for the inexpensive production of HA. Biological sources, such as fish scales, fish bones, bovine bones, egg shells, snail shells, teeth and bones of pig, are among the major sources of natural HA [1,2,25,[53][54][55][56][57][58][59]. Fish scales contain abundant valuable organic and inorganic components, mainly collagen and HA [60].…”
Section: Natural Hydroxyapatitementioning
confidence: 99%
See 2 more Smart Citations
“…However, in consideration of the high cost associated with chemicals used in the synthetic process, other natural sources were explored for the inexpensive production of HA. Biological sources, such as fish scales, fish bones, bovine bones, egg shells, snail shells, teeth and bones of pig, are among the major sources of natural HA [1,2,25,[53][54][55][56][57][58][59]. Fish scales contain abundant valuable organic and inorganic components, mainly collagen and HA [60].…”
Section: Natural Hydroxyapatitementioning
confidence: 99%
“…Direct burning is an easy and cheap way of obtaining natural HA. Fish scales are burned at high temperature to remove organic component, and HA is retained as ash [53,56,57,61]. Rosen et al [62] studied the characteristics of HA from processed bone and found that the bone HA exhibits significant differences in crystal morphology compared with synthetic HA.…”
Section: Natural Hydroxyapatitementioning
confidence: 99%
See 1 more Smart Citation
“…Kongsri et al [23] and Panda et al [24] extracted from fish scales, and Venkatesan et al [25] extracted from the fish bone. Furthermore, Zainon et al [26] and Kim et al [27] extracted from the cuttle fish bone. Chattanathan et al [28] used the catfish bone.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (HAP), with a chemical formula of Ca 10 (PO 4 ) 6 (OH) 2 , is one of constituent that had found in either in human bone or teeth and the major elements are including calcium and phosphorous. HAp is derived from natural materials such as fish bone (Jensen et al, 1996;Ozawa and Kanahara, 2005) and fish scale (Mondal et al, 2010;Zainon et al, 2012), bovine sources (Sofronia et al, 2014). Bovine and pork origins are often associated with disease transmission and religious sentiments (Gómez-Guillén et al, 2011).…”
Section: Introductionmentioning
confidence: 99%